Microbiological Sealing Analysis of a Tapered Connection and External Hexagon System - Gardel Nepomuceno Costa; Elizabeth Ferreira Martinez; Aluísio Martins de Oliveira Ruellas; Daiane Cristina Peruzzo; Júlio Cesar Joly; Marcelo Henrique Napimoga (International Journal of Dentistry)
Considering the variety of implant connection systems available in the market and the contrasting literature regarding tapered connection systems in terms of bacterial leakage, the aim of this in vitro study was to compare the effectiveness of the bacterial seal at the implant/abutment interface between an external hexagon and a tapered connection system. Twelve sets of indexed tapered connection components and twelve sets of external hexagon connection components were used for microbiological analysis. In addition, for each model, an implant with its respective prosthetic abutment was used as a negative control and another as a positive control of microbial contamination. Failure of the abutment/implant interface seal was observed via turbidity or presence of deposits in the culture. Descriptive analysis of the data and relative frequency (percentage) as well as Fisher’s exact test were used at a significance level of 5%. Two of ten (20%) external hexagon specimens showed contamination against 0/10 (0%) tapered connection implants. In conclusion, both implant/abutment connections were able to prevent bacterial leakage in vitro.